Análisis jurídico de la solicitud de aplicación de providencias preventivas en los juicios ejecutivos en relación con la cuantía de la demanda. - López Roldan Alex Rubén (2024)
An executive judgment is a type of judicial process that is initiated with the objective of obtaining the forced compliance of obligations that are clearly expressed and enforceable. This type of judgment is based on an executive title, which contains a clear, pure, determined and currently enforceable obligation to pay an amount of money or to perform a specific act. Based on the executive title, the actor (creditor) requests the judge to order forced execution against the defendant (debtor) to satisfy the pending obligation. The executive judgment is an agile and rapid procedural mechanism intended to enforce credit rights effectively, without an in-depth examination of the foundations of the debt, since these are presumed to be established in the title that originates the execution. Preventive orders are temporary precautionary measures that a judge can dictate within a judicial process, such as executive trials, to ensure the effectiveness of the ruling and protect the interests of the plaintiff while the case is resolved. In the context of the General Organic Code of Procedures, preventive measures may include the prohibition of alienating the defendant's assets, the seizure of bank accounts or the seizure of movable and immovable property. The preventive measures are established in Art. 124 and following of the General Organic Code of Processes, these measures are instituted as a means of ensuring that the assets owned by the debtor are not alienated or encumbered in the right of ownership, so that If necessary, the creditor may request the administration of justice to apply preventive measures for a subsequent seizure or auction of the assets, if applicable. With the application of preventive measures, what is sought is that the 4 creditor has a means to collect the debt, if he had no other way to comply with the obligation, when the amount of the claim is lower than the value of the encumbered asset. by preventive providence. Keywords: executive process, preventive measures, amount of the claim.